“Friends and foes” of multiple myeloma measurable/minimal residual disease evaluation by next generation flow - Pacelli, Paola; Raspadori, Donatella; Bestoso, Elena; Gozzetti, Alessandro; Bocchia, Monica (Frontiers in Oncology, 2022)
Next Generation Flow (NGF) represents a golden standard for the evaluation of Minimal Residual Disease (MRD) in Multiple Myeloma (MM) patients at any stage of treatment. Although the assessment of MRD is still not universally employed in clinical practice, numerous studies have demonstrated the strength of MRD- as a reliable predictor of long-term outcome, and its potential to supersede the prognostic value of CR. The possibility to acquire millions of events, in combination with the use of standard reagents and a good expertise in the analysis of rare populations, led to high chance of success and a sensitivity of 10-6 that is superimposable to the one of Next Generation Sequencing molecular techniques. Some minor bias, correlated to the protocols applied, to the quality of samples and to the high heterogeneity of plasma cells phenotype, may be overcome using standard protocols and having at disposition personnel expertise for MRD analysis. With the use of NGF we can today enter a new phase of the quantification of residual disease, switching from the definition of "minimal" residual disease to "measurable" residual disease. This review takes account of the principle “friends and foes” of Myeloma “Measurable” Residual Disease evaluation by NGF, to give insights into the potentiality of this technique. The optimization of the quality of BM samples and the analytic expertise that permits to discriminate properly the rare pathologic clones, are the keys for obtaining results with a high clinical value that could be of great impact and relevance in the future.